2007
DOI: 10.1017/s0022215107000382
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate analgesic prescription increases secondary post-tonsillectomy bleed rates: a completed audit loop

Abstract: A significantly greater than normal secondary haemorrhage rate was noted in patients who had undergone tonsillectomy or adenotonsillectomy as waiting list 'initiative' cases within an alternative healthcare provider setting, compared with patients undergoing the same surgery within a primary healthcare trust (17.8 vs 3.9 per cent, respectively; p 0.1). We conclude that adequate analgesia, for the first week post-tonsillectomy, is essential in order to keep the secondary haemorrhage rate within an acceptable ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Alhamarneh et al recently documented secondary post-tonsillectomy haemorrhage rates of 17.8% and 3.9% in two similar patient populations and concluded that the variability between the two groups was due to differences in pain management protocols. Inadequate pain control during the first post-operative week was more prevalent in the cohort with the higher bleed rate [16].…”
Section: Secondary Post-tonsillectomy Haemorrhagementioning
confidence: 87%
“…Alhamarneh et al recently documented secondary post-tonsillectomy haemorrhage rates of 17.8% and 3.9% in two similar patient populations and concluded that the variability between the two groups was due to differences in pain management protocols. Inadequate pain control during the first post-operative week was more prevalent in the cohort with the higher bleed rate [16].…”
Section: Secondary Post-tonsillectomy Haemorrhagementioning
confidence: 87%
“…, Sutters & Miaskowski , Hamers & Abu‐Saad , Huth & Broome , Wiggins & Foster ), as well as an increased risk of secondary haemorrhage (Alhamarneh et al . ). Importantly, studies report that one‐third of parents whose children underwent tonsillectomy further used other healthcare services to address concerns related to pain and postoperative management (Warnock & Lander , Swallow et al .…”
Section: Introductionmentioning
confidence: 97%
“…The situation is suboptimal as it has a significant impact on the child's convalescence and can lead to poor pain management, dehydration, inadequate rest periods, poor sleep quality, nausea and vomiting (Kotiniemi et al 1997, Sutters & Miaskowski 1997, Hamers & Abu-Saad 2002, Huth & Broome 2007, Wiggins & Foster 2007, as well as an increased risk of secondary haemorrhage (Alhamarneh et al 2008). Importantly, studies report that one-third of parents whose children underwent tonsillectomy further used other healthcare services to address concerns related to pain and postoperative management (Warnock & Lander 1998, Swallow et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Such examples have been demonstrated in physiologic systems 13 . Explanations for why patients hemorrhage after their tonsillectomy have included surgical technique, postoperative infection, and postoperative analgesia 14–17 . It may be more appropriate to consider this complication as a consequence of properties intrinsic and fundamental to the operation and healing process when viewed as a complex system.…”
Section: Discussionmentioning
confidence: 99%